Strategi Dinas Kesehatan Provinsi Lampung dalam Menanggulangi Penyebaran HIV/AIDS di Provinsi Lampung - Sintia Ranti; Dedy Hermawan; Ita Prihantika (Jurnal Administrativa, 2020)
The increase in population growth in Indonesia is one of the impacts for the transmission of HIV/AIDS. The high spread of HIV/AIDS in Lampung Province led the Minister of Health to form Permenkes Number 21 of 2013 concerning HIV/AIDS Prevention. This study aims to find alternative strategies for the Health Agency of Lampung Local Goverments in treating the spread of HIV/AIDS by paying attention to the management strategies implemented by the Lampung Provincial Health Office. However, currently the Lampung Provincial Health Office does not yet have a specific strategy to tackle the spread of HIV / AIDS. In addition, the lack of public knowledge about HIV / AIDS becomes an obstacle in efforts to tackle HIV / AIDS. Therefore, the aim of the authors in this study is to find the right strategy in tackling the spread of HIV / AIDS in Lampung Province. The type of research used is descriptive research with a qualitative approach. Data collection is done by means of interviews, questionnaires, and documentation. The theory used in identifying strategies is the analysis of internal and external environmental factors according to the theory put forward by Akdon. The results of the research indicates that human resources in handling HIV and AIDS are capable in terms of numbers and abilities. However, external conditions such as politics, law, and technology have constraints from the external environment that hinder the effectiveness of HIV/AIDS treatment. In accordance with Akdon's theory, the right strategy is to utilize human resources while collaborating with organizations that support to tackle the spread of HIV / AIDS. This is in line with strategies that minimize weaknesses and avoid threats.